Rural active aging as a development strategy: Nexus of physical exercise participation and multidimensional poverty in China - Qifei Xia; Shu Xuan; Guoyou Qin (PLoS ONE, 2025)
Background This study aims to assess the intrinsic links between physical exercise and multidimensional poverty among rural older people, focusing on the mediating mechanisms of social and cultural capital, to inform responses to active ageing. Methods This study utilized the adult and household databases of the China Household Tracking Survey (CFPS) in 2018 and 2022. Stata17.0 was used to screen and process the data, and the A-F double critical value method was adopted to measure and structurally decompose the multi-dimensional poverty among the elderly of Chinese household farmers. The association between physical exercise participation and multi-dimensional poverty among rural elderly people was estimated using the ordinary Least squares (OLS) method. The mediating effects of social capital and cultural capital were explored by using the stepwise regression method. Finally, the heterogeneous manifestations of the impact of physical exercise participation on multi-dimensional poverty among rural elderly people were investigated by using the grouped regression method. Results This study found that physical exercise participation has a significant role in reducing multidimensional poverty in old age among family farmers (β = −0.0149, p < 0.001), and this finding remains valid after a series of robustness tests such as full model estimation (β = −0.009, p < 0.001), propensity score matching test (ATT value of −0.017, −0.015, and −0.017, respectively) and other series of robustness tests, the conclusion still holds. The results of the mediating effect showed that social capital and cultural capital mediated the effect of physical exercise on multidimensional poverty. Heterogeneity analyses showed that the effects of physical exercise participation on multidimensional poverty were more pronounced among females, unmarried, in the eastern region, and among the elderly with a high life expectancy. Conclusion Participation in physical exercise can effectively alleviate multidimensional poverty, which is reflected in the enhancement of health level, economic status, living standard, and subjective perception sub-dimensions. Engaging in physical exercise can alleviate poverty through two channels: accumulating social capital and enhancing cultural capital. The construction and maintenance of rural sports facilities should be strengthened, a ‘healthy labour model’ combining physical exercise and agricultural production should be constructed, special sports poverty-alleviation initiatives should be implemented for “vulnerable” elderly people, and a ‘Healthy Villages’ project should be launched to promote the participation of all people in poverty alleviation. The ‘Healthy Villages’ programme has been launched to promote the participation of the entire population in physical exercise.